Electrochemical Characterization and Dating of Archaeological Leaded Bronze Objects Using the Voltammetry of Immobilized Particles. (20th April 2017) - Doménech‐Carbó, A.; Doménech‐Carbó, M. T.; Redondo‐Marugán, J.; Osete‐Cortina, L.; Barrio, J.; Fuentes, A.; Vivancos‐Ramón, M. V.; Al Sekhaneh, W.; Martínez, B.; Martínez‐Lázaro, I.; Pasíes, T.
Abstract : The application of solid state electrochemistry techniques for the characterization and dating of leaded bronze objects is described. Characteristic voltammetric signatures of copper and lead corrosion products were used as markers of more or less prolonged corrosion periods. The proposed methodology was applied to samples from the Roman archaeological sites of Valeria (Spain) and Gadara (Jordan), Roman and medieval sites in Xàtiva (Spain), and modern statuary exhibited outdoors, on the campus of the Universitat Politècnica of Valencia, Spain, covering a time interval between the fourth to second centurybc and the 20th centuryad . For such samples, the ratio between the signals for copper and lead corrosion products decreased monotonically with the corrosion time. This variation was modelled on the basis of thermochemical and kinetic considerations, the experimental data being consistent with a potential rate law for the corrosion process.